Migration on the Rise, a Paradigm in Decline: The Last Half-Century of Global Mobility - Michael A. Clemens (Institute of Labor Economics (IZA), 2022)
The past several decades have witnessed a rebirth of global labor mobility. Workers have begun to move between countries at rates not seen since before World War One. During the same period, economists' study of international migration has been framed by a particular textbook model of location choice. This paper reviews the evidence on the economic causes and effects of global migration during the past half century. That evidence falsifies most of the core predictions of the old model. The economics of migration will regain vitality and relevance by discarding and replacing its outworn paradigm.
Keywords: F22; J61; O15; 330; globalization; production; roy model; employment; wages; impact; selection; emigration; immigration; labor; history